Perception Of The Use Of Literary Texts In Learning Arabic Syntax: Study At Kolej Universiti Islam Perlis (KUIPs)/ تصورات استخدام النصوص الأدبية في دراسة النحو العربي: جامعة برليس الإسلامية أنموذجا - Lubis Safian, Nursafira; Mohd Bulkhaini, Siti Amirah Nurul 'Ain; Mustapha, Nik Hanan; Abul Hassan Ashari, Mohamad Zulfazdlee; Ismail, Khairul Hakimi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
This study aims to identify the perceptions of Arabic language students and teachers about using literary texts in the study of Arabic Syntax. To achieve the research objectives, the researcher relied on the analytical approach with the qualitative approach, which collected data using semi-structured interviews with eight students specializing in Arabic and four Arabic language teachers at Perlis Islamic University College (KUIPs) Malaysia. The audio data is transferred to the written text and encoded manually. One of the most important findings of the research is that the students agreed that the employment of literary texts in the study of Arabic grammar helps them practice the language daily through the methods used and master the Arabic grammar by parsing words correctly, and this differs from using ordinary texts because they did not feel enthusiastic and fun while studying Arabic Syntax. Teachers also agreed that employing literary texts in the process of teaching Arabic Syntax helps students to know the correct style of Arabic, as most of the literary language is an eloquent language, and that employing literary texts with examples selected from prose texts and poetic texts, all of which are familiar and usual for students specializing in Arabic language and literature. Based on this, teachers should pay attention to choosing appropriate literary materials, such as short stories, when teaching Arabic Syntax to ensure that students understand the rules better and practice them on the ground.